Optimization of Motivation and Learning Outcomes in Civic Education through TSTS Learning Model: Optimalisasi Motivasi dan Hasil Belajar Pendidikan Kewarganegaraan melalui Model Pembelajaran TSTS - Sulastri; Sucipto; Purnamasari, Hetty; Suciati (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Quality education plays a critical role in shaping democratic citizens with strong national identities. Specific Background: In Indonesian elementary schools, particularly in the subject of Pancasila and Civic Education (PPKn), students often exhibit low motivation and suboptimal learning outcomes due to conventional teaching methods. Knowledge Gap: Limited empirical research has explored the effectiveness of the Two Stay Two Stray (TSTS) cooperative learning model in addressing these issues in early-grade civic education. Aims: This study aims to evaluate the effectiveness of the TSTS model in enhancing student motivation and learning outcomes in PPKn among first-grade students at SDN Palengaan Daya 4. Results: Using a descriptive quantitative approach involving 30 students, the study found statistically significant improvements in both motivation and learning outcomes post-intervention, confirmed through paired t-tests (p < 0.05). Novelty: This research presents the first application of the TSTS model for first-grade civic education at SDN Palengaan Daya 4, offering empirical evidence of its pedagogical value. Implications: The findings support the Merdeka Belajar policy, promoting learner-centered approaches and collaborative environments, and recommend broader implementation of TSTS to foster active civic participation and character development in primary education.Highlight : The TSTS model significantly improves student motivation and learning outcomes in PPKn subjects. It supports the Merdeka Belajar policy by promoting a collaborative and engaging learning environment. Results show statistically significant improvements, indicating TSTS is a pedagogically effective strategy for early-grade civic education. Keywords : TSTS, Motivation, Learning Outcomes, Civic Education, Elementary School